Evaluation of Total Quality Management on Job Satisfaction and Performance of Private Bank Managers in East Java, Indonesia (International Conference of Graduate School on Sustainability (ICGSS), 2021)
The purpose of this research is to describe Total Quality Management, job satisfaction and manager's performance; analyze the effect of Total Quality Management on manager job satisfaction; analyze the effect of Total Quality Management on manager's performance; analyze the effect of job satisfaction on manager performance; analyze the effect of performance on manager job satisfaction; analyze the effect of Total Quality Management on performance through manager job satisfaction and analyze the effect of Total Quality Management on job satisfaction through the performance of private bank managers in East Java. This research uses explanatory research. The research population is all managers of private banks in East Java. This study used a Likert scale questionnaire which was distributed to 77 respondents. Random sampling technique was used to determine the respondents. This study concludes that between total quality management has a positive effect on job satisfaction and performance, satisfaction and performance can mediate total quality management on other exogenous variables.